2016
DOI: 10.1097/gme.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in midlife: the role of reproductive stage

Abstract: The slight, but not significant, excess of depressive symptoms during MT and early postmenopause cannot be attributed to a direct effect of reproductive status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Having persistent and/or troublesome VMS and sleep problems can make women feel stressed and irritable, which in turn can exacerbate menopausal symptoms. An estimated 9–10% of women report an increase in psychological symptoms, including depressed mood and/or anxiety, during the menopause transition (Almeida et al, 2016 ; Mishra & Kuh, 2012 ), which tends to be relatively transient, and is associated with troublesome VMS, current stress, low self‐esteem, and hormone fluctuations (Arnot, Emmott, & Mace, 2021 ; Campbell, Dennerstein, Finch, & Szoeke, 2017 ; Willi, Süss, Grub, & Ehlert, 2021 ). Longer duration of VMS has been linked with higher levels of perceived stress (Avis et al, 2015 ); acute psychological stress has been shown to provoke VMS (Swartzman, Edelberg, & Kemmann, 1990 ); there is also some evidence of altered physiological stress responsivity in women with VMS (Nathan et al, 2020 ).…”
Section: Figurementioning
confidence: 99%
“…Having persistent and/or troublesome VMS and sleep problems can make women feel stressed and irritable, which in turn can exacerbate menopausal symptoms. An estimated 9–10% of women report an increase in psychological symptoms, including depressed mood and/or anxiety, during the menopause transition (Almeida et al, 2016 ; Mishra & Kuh, 2012 ), which tends to be relatively transient, and is associated with troublesome VMS, current stress, low self‐esteem, and hormone fluctuations (Arnot, Emmott, & Mace, 2021 ; Campbell, Dennerstein, Finch, & Szoeke, 2017 ; Willi, Süss, Grub, & Ehlert, 2021 ). Longer duration of VMS has been linked with higher levels of perceived stress (Avis et al, 2015 ); acute psychological stress has been shown to provoke VMS (Swartzman, Edelberg, & Kemmann, 1990 ); there is also some evidence of altered physiological stress responsivity in women with VMS (Nathan et al, 2020 ).…”
Section: Figurementioning
confidence: 99%
“…Women with a history of depression or anxiety were more prone to develop mood symptoms during menopause. 3,9,12,15,17,22 A history of anxiety also increased the risk of development of depressive symptoms during menopause. 3,9 The prospective long-term Zurich study 12 demonstrated that neuroticism (a personality trait disposition to negative mood and anxiety) at age 30 significantly predicted increased prevalence of major depression and anxiety disorders during menopause.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Pimenta et al 8 showed that psychological symptoms were significantly elevated in peri-menopausal women compared to matched pre-menopausal women. Almeida et al 9 reported that reproductive status did not affect the prevalence of MDD, but when contrasted with pre-menopause, the peri-menopausal phase was associated with an elevated risk of developing depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although depressive symptoms during the menopausal transition cannot be attributed directly to the reproductive status [12], women with a depressive episode earlier in life show a higher risk for the recurrence of depressive symptoms during the perimenopause [13][14][15]. However, even women who have been mentally healthy throughout their life may experience negative mood states through to depression during this phase [10,11,16,17].…”
Section: Introductionmentioning
confidence: 99%